2010
DOI: 10.1007/s10531-010-9848-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of midsized to large-bodied mammals in Amazonian landscapes under varying contexts of forest cover

Abstract: Both forest fragmentation and overhunting have profound effects on the structure of large-vertebrate assemblages in neotropical forests. However, the long-term value of habitat fragments for forest mammals remains poorly understood and few regional scale studies have replicated sampling across spatially independent landscapes. Here, we assess the species occupancy and abundance of midsized to large-bodied mammals within three neighbouring Amazonian forest landscapes varying widely in extent of forest cover. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 57 publications
7
44
0
9
Order By: Relevance
“…The impacts of habitat fragmentation limit the presence of various species in the fragment because they restrict the area of the fragment (Chiarello 1999, Michalski & Peres 2007. They also cause edge effects (Fahrig 2003) in the interaction between the fragment and the matrix (Murcia 1995, Stevens & Husband 1998 and decrease landscape connectivity (Fahrig & Merriam 1994, Sampaio et al 2010. Aside from these factors, there are also factors present related to the proximity of households and urban centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impacts of habitat fragmentation limit the presence of various species in the fragment because they restrict the area of the fragment (Chiarello 1999, Michalski & Peres 2007. They also cause edge effects (Fahrig 2003) in the interaction between the fragment and the matrix (Murcia 1995, Stevens & Husband 1998 and decrease landscape connectivity (Fahrig & Merriam 1994, Sampaio et al 2010. Aside from these factors, there are also factors present related to the proximity of households and urban centers.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario the fragments are important to conserve despite their size or location, because although they are small, they may have conservation value in increasing connectivity (e.g. Crooks 2002, Lacerda et al 2009, Sampaio et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies (Mendes Pontes 2004, Mendes Pontes et al 2007, Mendes Pontes et al 2012, Melo et al 2015, we showed that in the highly heterogeneous vegetation mosaics of the northernmost Guyana shield the structure of the terrestrial mammalian assemblages was shaped by forest type and heterogeneity, which, in turn, is directly connected with resource availability. Species richness and diversity may vary between protected and impacted areas, with the latter in most studies presenting a lower number of species due to hunting (Lopes and Ferrari 2000, Peres and Nascimento 2006, Michalski and Peres 2007, Sampaio et al 2010, Ahumada et al 2011, Melo et al 2015, Meyer et al 2015. Accordingly, the richest area was PA Uatumã, located south of the Guyana shield, closest to central Amazonia, the natural vegetation cover for which is dense ombrophilous forests, followed by IA Entre Rios, which is located in the transition between the dense ombrophilous terra firme forests of the south of the Guyana shield, and the seasonally-dry forest mosaics of central Guyana shield, and the poorest areas were PA Maracá and IA Bom Jesus, in the northernmost Guyana shield, where the vegetation is mainly seasonally-dry forest mosaics interspersed with extensive areas of savannas (See Hoorn et al (2010)).…”
Section: Determinants Of the Structure Of The Mammalian Assemblagesmentioning
confidence: 99%
“…Indeed, pumas (Puma concolor) and jaguars (Panthera onca) need an area of at least 1000 ha to have 50% probability of occurrence in the same study region . These species require large areas effectively protected to maintain viable populations in the long term, disappearing in fragmented habitats that are not connected by corridors (Crooks 2002;Sampaio et al 2010;Sálek et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Obtaining data of species occurrence through local interviews is an effective approach successfully tested with mid-sized and large bodied vertebrates (Gros 1998;Lawes et al 2000;Urquiza-Haas et al 2009;Sampaio et al 2010). …”
Section: Survey Richness Of Large Vertebratesmentioning
confidence: 99%